Ngunying From Ritual To Music Composition | Ngunying Dari Ritual Menjadi Kompoisisi Musik - Wardizal Wardizal (GHURNITA: Jurnal Seni Karawitan, 2021)
"Ngunying" is a form of sacred tradition that grows and develops in the midst of the socio-cultural life of the people of Bangli Regency. Ngunying is a ritual as a form of community offering in Bebalang Village to Sang Hyang Widhi Wasa. The ngunying tradition is a gift by Ida Betara Durga, because the ngunying tradition can be used as a neutralizer of the universe from the disturbance of the bhuta kala. It is believed that after the implementation of this procession the community will find peace, balance, and harmony in the village. The Ngunying tradition as a ritual and sacred ceremony is interesting to be transformed into a musical composition. In that context, the musical composition with the title "Ngunying" was created for the purposes of the Final Project examination at the Karawitan Art Study Program, Faculty of Performing Arts, ISI Denpasar. Even semester of academic year 2020/2021.. This work is in the form of percussion pategak bebarongan creations with the media expressing the gamelan semar pagulingan saih pitu. Given the Covid-19 pandemic situation, then. This work uses a sample of the gamelan tone of Semar Pagulingan Saih Pitu which is then processed, processed or poured into the FL Studio and Cubade 5 multimedia applications.